Full validation of therapeutic antibody sequences by middle-up mass measurements and middle-down protein sequencing. Issue 2 (17th February 2016) - Resemann, Anja; Jabs, Wolfgang; Wiechmann, Anja; Wagner, Elsa; Colas, Olivier; Evers, Waltraud; Belau, Eckhard; Vorwerg, Lars; Evans, Catherine; Beck, Alain; Suckau, Detlev
ABSTRACT: The regulatory bodies request full sequence data assessment both for innovator and biosimilar monoclonal antibodies (mAbs). Full sequence coverage is typically used to verify the integrity of the analytical data obtained following the combination of multiple LC-MS/MS datasets from orthogonal protease digests (so called "bottom-up" approaches). Top-down or middle-down mass spectrometric approaches have the potential to minimize artifacts, reduce overall analysis time and provide orthogonality to this traditional approach. In this work we report a new combined approach involving middle-up LC-QTOF and middle-down LC-MALDI in-source decay (ISD) mass spectrometry. This was applied to cetuximab, panitumumab and natalizumab, selected as representative US Food and Drug Administration- and European Medicines Agency-approved mAbs. The goal was to unambiguously confirm their reference sequences and examine the general applicability of this approach. Furthermore, a new measure for assessing the integrity and validity of results from middle-down approaches is introduced – the "Sequence Validation Percentage." Full sequence data assessment of the 3 antibodies was achieved enabling all 3 sequences to be fully validated by a combination of middle-up molecular weight determination and middle-down protein sequencing. Three errors in the reference amino acid sequence of natalizumab, causing a cumulative mass shift of only −2 Da in the natalizumab Fd domain, were corrected as a result of this work.